In search of scandal - Lord, Susanne (Sourcebooks Casablanca, 2015)
"All of London is abuzz with the tale of Will Repton. The lone survivor of a massacre in Tibet has returned to England a hero, but the traumatized explorer has no time for glory. Another dangerous expedition awaits. Nothing will deter him from his quest, and no one will unearth his secret-until Will meets Charlotte Baker. Vivacious Charlotte Baker also has a mission-to find a man whose bold spirit matches her own. When she meets Will Repton, she immediately recognizes him as her soul mate, and she's naively willing to turn her back on the rules of propriety to ensnare him. Will is torn between his fascination with Charlotte and his vow to finish his quest. He knows what it is to risk life and limb-but what if his most perilous adventure doesn't lie across an ocean, but within his own lost heart?"--Page [4] of cover